2018
DOI: 10.1016/j.jesf.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional movement screen comparison between the preparative period and competitive period in high school baseball players

Abstract: Background/ObjectiveAlthough the functional movement screen (FMS) has been widely applied for screening athletes, no previous study has used FMS scores to examine the association between distinct training seasons in high school baseball players. The aims of this study were to ascertain the functional movement screen (FMS) scores differences between the preparative period (PPP) and the competitive period (CPP) among high school baseball players and further determine whether FMS can be used as a tool to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The motion of sprinting involves the participation of various biomechanical factors throughout the body (Mero et al, 1992), while efficient and fast execution of sprint action requires not only strength but also sufficient mobility and stability (García-Pinillos et al, 2015; Nesser et al, 2008; Seitz et al, 2014). The FMS is a tool designed to assess movement, and the individual tests included in the FMS have a balance between mobility and stability as a basic requirement (Lee et al, 2018). Therefore, higher FMS total scores could have a positive effect on sprint time records.…”
Section: Discussionmentioning
confidence: 99%
“…The motion of sprinting involves the participation of various biomechanical factors throughout the body (Mero et al, 1992), while efficient and fast execution of sprint action requires not only strength but also sufficient mobility and stability (García-Pinillos et al, 2015; Nesser et al, 2008; Seitz et al, 2014). The FMS is a tool designed to assess movement, and the individual tests included in the FMS have a balance between mobility and stability as a basic requirement (Lee et al, 2018). Therefore, higher FMS total scores could have a positive effect on sprint time records.…”
Section: Discussionmentioning
confidence: 99%
“…The score for each item ranges from 0 to 3, with 0 indicating pain, 1 indicating a noncompleted skill performance, 2 indicating a skill performance with compensation, and 3 indicating a skill performance without compensation. The maximum score for the FMS is 21, and a total score lower than or equal to 14 points on the FMS indicates a greater possibility of sustaining a sports injury [13]. The FMS has exhibited excellent interrater reliability (0.97) for examining adolescents [14].…”
Section: Assessmentsmentioning
confidence: 99%
“…This is consistent with other studies that have found that FMS score does not predict injury. 30,41,42…”
Section: Discussionmentioning
confidence: 99%